Correlation between in vivo and in vitro functional tests for activated macrophages. - Rhodes, J M (1979)
Mice undergoing graft-versus-host reaction, skin grafting, and inoculation with tumor cells were tested for nonspecific resistance by intravenous challenge with Listeria monocytogenes. Peritoneal exudate macrophages from mice treated in a similar manner were tested in vitro for increased degradation of [1-14C]glucose, ability to degrade antigen/antibody complexes, ability to inhibit intracellular growth of listeria, and staining for beta-galactosidase. There was good correlation between in vivo resistance towards L. monocytogenes and in vitro inhibition of intracellular growth. There was also good correlation between increase in beta-galactosidase and in vivo resistance in mice undergoing a graft-versus-host-reaction.